The Science of Near-Death Experiences - Moody, Raymond A., Jr; Hagan, John C. (Book collections on Project MUSE., 2017)
"What happens to consciousness during the act of dying? The most compelling answers come from people who almost die and later recall events that occurred while lifesaving resuscitation, emergency care, or surgery was performed. These events are now called near-death experiences (NDEs). As medical and surgical skills improve, innovative procedures can bring back patients who have traveled farther on the path to death than at any other time in history. Physicians and healthcare professionals must learn how to appropriately treat patients who report an NDE. It is estimated that more than 10 million people in the United States have experienced an NDE. Hagan and the contributors to this volume engage in evidence-based research on near-death experiences and include physicians who themselves have undergone a near-death experience. This book establishes a new paradigm for NDEs."--